2006
DOI: 10.1021/jf061108m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soy Aglycon Isoflavones on Bone-Related Traits and Lens Protein Characteristics of Ovariectomized Rats and Bioactivity Performance of Osteoprogenitor Cells

Abstract: Health benefits of soy isoflavones have attracted the concern of the public and the interest of health-care professionals. In this study, two trials were conducted in characterizing bone-related traits and lens proteins as affected by supplementation of soy aglycon isoflavones (SAI). In trial 1, an in vivo study, 20 Sprague-Dawley rats were ovariectomized (OVX) and randomly distributed into OVX and OVX+SAI (135 mg of SAI/kg of feed; 8.33 mg/kg body weight; 2.5 mg/day) groups. Another group containing 10 rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The in vitro study with osteoprogenitor cells revealed that cell viability, alkaline phosphatase activity, osteocalcin, and Ca contents of the SAI-supplemented group were higher than those of the unsupplemented group. 39 In the fermented milks, daidzein is the most abundant isoflavone, and it can be further metabolized to equol, a compound with greater estrogenic activity than other isoflavones. The combination of purified daidzein and high Ca in OVX mice favorably protected against the loss of femur and vertebrae BMD and biomechanical strength at multiple skeletal sites.…”
Section: ' Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro study with osteoprogenitor cells revealed that cell viability, alkaline phosphatase activity, osteocalcin, and Ca contents of the SAI-supplemented group were higher than those of the unsupplemented group. 39 In the fermented milks, daidzein is the most abundant isoflavone, and it can be further metabolized to equol, a compound with greater estrogenic activity than other isoflavones. The combination of purified daidzein and high Ca in OVX mice favorably protected against the loss of femur and vertebrae BMD and biomechanical strength at multiple skeletal sites.…”
Section: ' Discussionmentioning
confidence: 99%
“…Osteopenia increases with bone turnover rate and with resorption exceeding formation . Influence of soy aglycon isoflavones (SAI) on bone-related traits and lens protein characteristics of ovariectomized rats and bioactivity performance of osteoprogenitor cells were investigated by Lien et al This in vivo study indicated that daily body weight gains in the OVX and OVX + SAI groups were greater than that of the SHAM group. Bone ash and Ca contents of the SHAM and OVX + SAI groups were higher than those of the OVX group.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In contrary to estrogen, which mediates osteoclasts to release calcium from bone, Lien et al reported that bone ash and calcium contents were higher in SI-treated OVX rats. 39 The in vitro study conducted by the same group found that SI-treated osteoprogenitor cells had a higher viability, ALP activity, OC, and calcium content. 39 It has also been shown that GEN can decrease bone turnover by stimulation of cadmium (Cd) excretion while inhibiting calcium excretion from bone in Cd/OVX rats.…”
mentioning
confidence: 99%
“…39 The in vitro study conducted by the same group found that SI-treated osteoprogenitor cells had a higher viability, ALP activity, OC, and calcium content. 39 It has also been shown that GEN can decrease bone turnover by stimulation of cadmium (Cd) excretion while inhibiting calcium excretion from bone in Cd/OVX rats. 40 Interestingly, there exists different dose responses between calcium concentration and a gradual increased dose of supplementary equol (a metabolite of SI) in OVX rats.…”
mentioning
confidence: 99%
“…Mathey et al 28) reported that isoflavone aglycone administration improved bone mineral density in OVX rats. Lien et al 29) reported that dietary ingestion of aglycone had a favorable effect on bone mineral contents in OVX rats. In addition, Kawakami et al 30) compared the effects of aglycone and glycoside on lipid metabolism in rats and suggested the superiority of aglycone.…”
Section: Discussionmentioning
confidence: 99%